Impact of deep phenotyping: high diagnostic yield in a diverse pediatric population of 172 patients through clinical whole-genome sequencing at a single center - Akgun-Dogan, Ozlem; Tuc Bengur, Ecenur; Ay, Beril; Ozkose, Gulsah Sebnem; Kar, Emre; Bengur, Fuat Baris; Bulut, Aybike S.; Yigit, Ayca; Aydin, Eylul; Esen, Fatma Nisa; Ozdemir, Ozkan; Yesilyurt, Ahmet; et al. (Frontiers in Genetics, 2024)
Background: Pediatric patients with undiagnosed conditions, particularly those suspected of having Mendelian genetic disorders, pose a significant challenge in healthcare. This study investigates the diagnostic yield of whole genome sequencing (WGS) in a pediatric cohort with diverse phenotypes, particularly focusing on the role of clinical expertise in interpreting WGS results. Methods: A retrospective cohort study was conducted at Acibadem University's Maslak Hospital in Istanbul, Turkey, involving pediatric patients (0-18 years) who underwent diagnostic WGS testing. Clinical assessments, family histories, and previous laboratory and imaging studies were analyzed. Variants were classified and interpreted in conjunction with clinical findings. Results: The cohort comprised 172 pediatric patients, aged 0-5 years (62.8%). International patients (28.5%) were from 20 different countries. WGS was utilized as first-tier in 61.6% of patients. The diagnostic yield of WGS reached 61.0%, enhanced by the reclassification of variants of uncertain significance (VUS) through reverse phenotyping by an experienced clinical geneticist. Consanguinity was 18.6% of the overall cohort. Dual diagnoses were present in 8.5% of solved patients. Discussion: Our study particularly advocates for the selection of WGS as a first-tier testing in infants and children with rare diseases under 5 years of age, thereby potentially shortening the duration of the diagnostic odyssey. The results also emphasize the critical role of a single clinical geneticist's expertise in deep phenotyping and reverse phenotyping, which contributed significantly to the high diagnostic yield.